2011
DOI: 10.1093/gbe/evr067
|View full text |Cite
|
Sign up to set email alerts
|

A Massively Parallel Sequencing Approach Uncovers Ancient Origins and High Genetic Variability of Endangered Przewalski's Horses

Abstract: The endangered Przewalski's horse is the closest relative of the domestic horse and is the only true wild horse species surviving today. The question of whether Przewalski's horse is the direct progenitor of domestic horse has been hotly debated. Studies of DNA diversity within Przewalski's horses have been sparse but are urgently needed to ensure their successful reintroduction to the wild. In an attempt to resolve the controversy surrounding the phylogenetic position and genetic diversity of Przewalski's hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…This finding is in agreement with the observation that virtually all Przewalski's horse control region haplotypes belong to haplogroup F, with one notable exception (AF055879) (23). Recently, four complete Przewalski mtDNAs were published (24). Although three mtDNAs belonged to haplogroup F, the fourth mtDNA shared the control region motif with the above-mentioned sample AF055879, radiating before the J'K node in our phylogeny (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 92%
“…This finding is in agreement with the observation that virtually all Przewalski's horse control region haplotypes belong to haplogroup F, with one notable exception (AF055879) (23). Recently, four complete Przewalski mtDNAs were published (24). Although three mtDNAs belonged to haplogroup F, the fourth mtDNA shared the control region motif with the above-mentioned sample AF055879, radiating before the J'K node in our phylogeny (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 92%
“…We first compared the 16 complete mitochondrial sequences characterized here (SI Appendix, section S5.1) with complete mitochondrial sequences from 27 ancient and 78 present-day horses (14,18,(23)(24)(25)(26)(27)(28). Maximum likelihood (ML) and Bayesian phylogenetic inference showed that the Yakutian mitochondrial haplotypes of specimens Yak1-Yak7, Yak9, and CGG101397 are closely related to the mitochondrial haplotypes of domesticated breeds (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, all the 150 complete mtDNA genome sequences available from literature [NC_001640 (Xu and Arnason, 1994); EF597512-14 (Xu et al, 2007); AP012267-70 (Goto et al, 2011); EU939445 (Jiang et al, 2011); HQ439441-500 (Lippold et al, 2011);and JN398377-457 (Achilli et al, 2012)] were used to obtain more reliable and informative HVS-I patterns of sites defining haplogroups.…”
Section: Methodsmentioning
confidence: 99%